Implementasi Good Governance Dalam Pelayanan Publik di Kantor Kecamatan Semarang Timur - Agus Bahrudin; Susetyo Arief Hidayat (Public Service and Governance Journal, 2023)
The application of good governance in public services in the district is expected to create a government system that is more responsive, accountable and oriented to the interests of the community. This study aims to determine the application of the principles of good governance in public services in the East Semarang District Office of Semarang City as well as to find out the supporting and inhibiting factors. The research method used is descriptive qualitative with data collection techniques through in-depth interviews with informants, namely the district head, service section head and service users. The results of the study show that the principles of accountability have been implemented through coordination, program outreach, effective communication, officer competence, commitment, honesty and democracy, the principles of transparency have been implemented through information disclosure and easy access to services, democratic principles have been implemented through the involvement of officers, accountability, integrity, following up on public complaints and a straightforward mechanism. The application of the principle of the Rule of Law is carried out by providing services to the public that are fair and do not discriminate, employees carry out their duties in accordance with existing rules. Factors supporting the implementation of good governance in the East Semarang District Office are effective communication; adequate resources; disposition shows honesty, commitment, and democracy; The bureaucratic structure is reflected in the program implementation mechanism according to the Standard Operating Procedure (SOP) and is easy to understand as stated in the program/policy guidelines and implementing organizational structure. The obstacles are the lack of understanding by the apparatus of the principles of Good Governance, inadequate facilities and lack of discipline by the apparatus during working hours and the lack of community participation.